Benign pulmonary metastasizing leiomyomatosis: report of 3 cases and review of the literature - Araujo, Naiana Mota (2024)
Benign pulmonary metastasizing leiomyomatosis (BPML) is a rare condition, most commonly found in premenopausal women in reproductive age with a history of hysterectomy for uterine leiomyoma or myomectomy. Most cases are asymptomatic and the diagnosis is usually incidental during routine examinations. Although the condition is benign, some patients may present with dyspnea and significant hypoxemia. The diagnosis is established through anatomopathological examination of the lung lesions. Treatment varies according to the clinical picture and the number and size of the lesions.